Ophthalmic aspects of aging - Kotarba, Agnieszka; Borowiak, Ewa; Czajkowski, Janusz (Nursing Problems / Problemy Pielęgniarstwa, 2014)
The authors present selected ophthalmological and psychological problems associated with aging of the human organism. They emphasize a role of significant changes occurring in the body that facilitate the formation of chronic eye diseases and a role of psychological support in the management of patients suffering from age-related macular degeneration (AMD) and primary open-angle glaucoma (POAG). The analysis of the literature reports and the authors’ own experience allow to draw the following conclusions: Although aging is an irreversible process, it can be slowed down through implementation of pro-healthy lifestyle, detection and treatment of acute and chronic ophthalmic diseases as well as social support. The process of eye aging is complicated and accompanied by a cascade of molecular, biochemical and hemodynamic changes involving all structures of the organ of vision. Patients with eye diseases usually become dependent on other people and the level of their life quality considerably decreases. An important aim of care for the elderly person provided by the medical personnel team should include early recognition of AMD and an increase in social awareness connected with this disease. Elderly subjects should be encouraged to more frequently visit the ophthalmologist and treat the identified dysfunction. Social support for patients and their close relatives is very helpful in their adjustment to vision disability and improves quality of life in patients as well as maintenance of at least partial social or even occupational activity.